Trametes robiniophila represses angiogenesis and tumor growth of lung cancer via strengthening let-7d-5p and targeting NAP1L1. Issue 3 (1st March 2022) - Gan, HuiZhu; Xu, XinXin; Bai, YinYin
ABSTRACT: Trametes robiniophila (Huaier) is available to refrain lung cancer (LC) cell progression, but its impact and mechanism on angiogenesis of LC are not proved. The study was to explore the potential mechanism of Huaier repressing angiogenesis and tumor growth in LC via strengthening let-7d-5p and targeting NAP1L1. Let-7d-5p and NAP1L1 expression was detected in LC tissues and cells (A549). Pretreatment of A549 cells was with Huaier. Transfection of changed let-7d-5p and NAP1L1 was to A549 cells to uncover their roles in LC cell progression with angiogenesis. Evaluation of the impact of let-7d-5p on angiogenesis in LC was in vitro in a mouse xenograft model. Identification of the targeting of let-7d-5p with NAP1L1 was clarified. The results clarified reduced let-7d-5p but elevated NAP1L1 were manifested in LC. Huaier restrained angiogenesis and tumor growth of LC in vivo and in vitro ; Augmented let-7d-5p or declined NAP1L1 motivated the therapy of Huaier on LC; Let-7d-5p negatively modulated NAP1L1; Elevated NAP1L1 reversed the influence of enhancive let-7d-5p. These results strongly suggest that Huaier represses angiogenesis and tumor growth in LC via strengthening let-7d-5p and targeting NAP1L1. Huaier/let-7d-5p/NAP1L1 axis is supposed to be a promising target for the treatment of angiogenesis and tumor growth in LC via elevated let-7d-5p and targeted NAP1L1.